A hitchhiking approach to reconstruct the finger pulp and the subsequent 1st toe hemi-pulp donor site defect. Issue 2 (February 2022) - Chu, Tinggang; Xiao, Jian; Tao, Zhengyu; Zheng, Zengming; Wang, Anyuan; Lin, Damu; Li, Zhijie; Chen, Xinlong; Gao, Weiyang
Summary: Background: The free 1st toe hemi-pulp transfer for finger pulp reconstruction was acknowledged as the optimal one. However, the treatment of the 1st toe donor defect, owning to the impossibility of primary closure, was frequently oversimplified. This study presented a "hitchhiking" approach to resurface finger pulp and the subsequent 1st toe donor site defect in a one-stage procedure. Methods: From 2014 to 2019, finger pulp amputations (13 digits in 12 patients) were reconstructed with free 1st toe pulp flaps, and the donor site was resurfaced by the 2nd toe pedicled flap with the 2nd toe's primary closure. Therapeutic evaluation of repaired fingers and toes was based on cold intolerance, two-point discrimination (2PD), and gait disturbance. Results: All finger and toe pulp flaps survived uneventfully. The average size of free 1st toe and pedicled 2nd toe flap was 3.1 cm × 2.0 cm (3.5 cm × 1.4 cm to 4.2 cm × 2.5 cm) and 3.0 cm × 1.1 cm (2.0 cm × 0.9 cm to 3.8 cm × 1.5 cm), respectively. The regained average static 2PD on the finger and 1st toe pulps was 6 mm (ranged 5–10 mm) and 4 mm (ranged 2–6 mm), respectively. All reconstructed 1st toe pulps were qualified for normal gait. One patient complained the mild cold intolerance, and hammer-toe deformities were involved in two cases. Conclusion: To fulfill donor site care and cost-effective rule, the toe-to-finger pulp reconstruction can't underestimate the morbidity on 1st toe donor site due to inappropriate intervention. Equally importantly, the hitchhiking pedicled 2nd toe flap should be recruited in the reconstructive scheme.